Handwritten Image Segmentation Carakan Madura Based Projection And Connected Component Labeling: Segmentasi Citra Tulisan Tangan Carakan Madura Berbasis Proyeksi Dan Connected Component Labeling - Miftah Farid; Joan Santoso; Endang Setyati (JOINCS (Journal of Informatics, Network, and Computer Science), 2020)
At the time the Carakan Madura is currently found on sign of street names in the Madura region. It is also found in the historical sites and museum. However, many people do not understand about Carakan Madura because it is rarely used in daily life. There are many ways to keep Carakan Madura sustainable and not extinct, including preservation and maintenance of historical objects and also from education. The maintenance of these historical objects is usually carried out in museums and places where historical objects, including the Sumenep palace museum and Asta Tinggi. In the Sumenep palace museum, documents with Carakan Madura are still stored. In the Asta tinggi there are also stone carvings with the words Carakan Madura. There are other important things in the preservation of Carakan Madura, namely that Carakan Madura is included in the local content education curriculum for Madura language so that students can learn about Carakan Madura properly and well so students are not only knowing, but also understanding. For this reason, tools are needed so that students can more understand the Carakan Madura. The purpose of this research is to segment of the Carakan Madura handwritten image based on projection and connected component labeling. The results of this research can be concluded that the segmentation process in Carakan Madura handwriting has been successfully carried out in the form of the composing characters of Carakan Madura.